Removing financial barriers to organ and bone marrow donation: The effect of leave and tax legislation in the US - Nicola Lacetera; Mario Macis; Sarah S. Stith (Institute for the Study of Labor (IZA), 2012)
In an attempt to alleviate the shortfall in organs and bone marrow available for transplants, many U.S. states passed legislation providing leave to organ and bone marrow donors and/or tax benefits for live and deceased organ and bone marrow donations and to employers of donors. We exploit cross-state variation in the timing and passage of such legislation to analyze its impact on organ donations by living and deceased persons, on measures of the quality of the organs transplanted, and on the number of bone marrow donations. We find that these provisions did not have a significant impact on the quantity of organs donated. The leave legislation, however, did have a positive impact on bone marrow donations. We also find some evidence of a positive impact on the quality of organ transplants, measured by post-transplant survival rates. Our results suggest that these types of legislation work for moderately invasive procedures such as bone marrow donation, but may be too low for organ donation, which is riskier and more burdensome to the donor.
Keywords: D64; H41; I12; J18; K32; 330; incentives; altruism; organ donation; bone marrow donation